Europe and China competing for Russian gas? - Roland Götz (Stiftung Wissenschaft und Politik (SWP), 2006)
When President Vladimir Putin visited Beijing on 21 March 2006 heading a delegation of 1000 government officials, many observers expected that he would finally sign the contracts for the East Siberian oil pipeline to China which had been under discussion for many years. Instead, he surprisingly offered the construction of a gas pipeline from West Siberia to China. Such a pipeline would affect European interests, because it is fed by Russia's main gas-producing region with its large gas pipelines going to the West. In this context the questions about Russia's future gas exporting potential and European alternatives for gas supply, raised by the International Energy Agency, become even more relevant topics.(SWP Comments / SWP)
Keywords: 320